2019
DOI: 10.1111/josh.12820
|View full text |Cite
|
Sign up to set email alerts
|

Noncomprehensive and Intermittent Obesity‐Related School Programs and Policies May Not Work: Evidence from the COMPASS Study

Abstract: BACKGROUND:The school environment has the potential to influence student body mass index (BMI) through programs and policies. Our objective was to examine the effect of modifying obesity-related school policies and programs on youths' BMI trajectories. METHODS:Obesity-related school policies and programs related to physical activity and healthy eating were collected from 41 schools across Ontario at baseline (2012-2013) and year 2 (2013-2014) of the COMPASS study. Self-reported height and weight were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Results obtained on these approaches are variable. Though usually favourable in the short term, they fail to modify behaviours effectively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained on these approaches are variable. Though usually favourable in the short term, they fail to modify behaviours effectively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Open access the population level, predominantly because the environmental context remains unchanged. 11 A WHO review concluded 'Environmental interventions targeting the built environment, policies that reduce barriers to physical activity, transport policies and policies to increase space for recreational activity have been demonstrated to be effective.' 12 There is widespread agreement that built environments can promote or hinder health behaviours and outcomes, and evidence exists for specific environmental features of importance.…”
Section: Introductionmentioning
confidence: 99%